Voltammetric immunoassay for the human blood clotting factor IX by using nanogapped dielectrode junctions modified with gold nanoparticle-conjugated antibody - Gopinath S.C.B.; Perumal V.; Rao B.S.; Md Arshad M.K.; Voon C.H.; Lakshmipriya T.; Haarindraprasad R.; Vijayakumar T.; Chen Y.; Hashim U. (Springer-Verlag Wien, 2024)
Indexed by SCOPUS/ERA